Randomized, double-blind, multicenter evaluation of pramipexole extended release once daily in early Parkinson's disease - Hauser, Robert A.; Schapira, Anthony H.V.; Rascol, Olivier; Barone, Paolo; Mizuno, Yoshikuni; Salin, Laurence; Haaksma, Monika; Juhel, Nolwenn; Poewe, Werner (Movement disorders, 2010)
The objective of this study was to evaluate the efficacy and safety of pramipexole extended release (ER) administered once daily in early Parkinson's disease (PD). Pramipexole immediate release (IR) administered three times daily (TID) is an efficacious and generally well‐tolerated treatment for PD. A pramipexole ER formulation is now available. We performed a randomized, double‐blind, placebo and active comparator–controlled trial in subjects with early PD. The primary efficacy and safety evaluation of pramipexole ER compared with placebo took place at week 18. Two hundred fifty‐nine subjects were randomized 2:2:1 to treatment with pramipexole ER once daily, pramipexole IR TID, or placebo. Levodopa rescue was required by 7 subjects in the placebo group (14%), 3 subjects in the pramipexole ER group (2.9%, P = 0.0160), and 1 subject in the pramipexole IR group (1.0%, P = 0.0017). Adjusted mean [standard error (SE)] change in Unified Parkinson Disease Rating Scale (UPDRS) II [activities of daily living (ADL)] + III (motor) scores from baseline to week 18, including post‐levodopa rescue evaluations, was −5.1 (1.3) in the placebo group, −8.1 (1.1) in the pramipexole ER group (P = 0.0282), and −8.4 (1.1) in the pramipexole IR group (P = 0.0153). Adjusted mean (SE) change in UPDRS ADL + motor scores, censoring post‐levodopa rescue data, was −2.7 (1.3) in the placebo group, −7.4 (1.1) in the pramipexole ER group (P = 0.0010), and −7.5 (1.1) in the pramipexole IR group (P = 0.0006). Adverse events more common with pramipexole ER than placebo included somnolence, nausea, constipation, and fatigue. Pramipexole ER administered once daily was demonstrated to be efficacious compared with placebo and provided similar efficacy and tolerability as pramipexole IR administered TID. © 2010 Movement Disorder Society